Photoluminescence and γ-Ray Induced Thermoluminescence Investigation of Phase Pure Cerium Doped Yttrium Silicate Nanophosphors - Dhanalakshmi, K.; Reddy, A. Jagannatha; Parashuram, L. (Asian Journal of Chemistry, 2019)
Y2SiO5:Ce3+ (1-7 mol %) nanophosphors were prepared by solution combustion method using oxalyldihydrazide fuel. The phosphors were characterized by X-ray diffraction, scanning electron microscopy, UV-visible and Fourier transform infrared spectroscopy. The XRD patterns confirm the monoclinic structure of the prepared phosphors, with crystallite size of 66-74 nm. The surface morphology and elemental composition were evaluated by SEM and energy dispersive X-ray analysis. The optical band gap was calculated and is between 4.66 eV – 4.9 eV. The presence of Si-O-Si and Y-O bonds was confirmed by the FTIR spectra. Effect of cerium concentration on photoluminescence and thermoluminescence intensity were interpreted. The photoluminescence emission spectrum was recorded under excitation wavelength of 370 nm, the emission spectra showed three significant peaks positioned at 418 nm, 459 nm and 485 nm, which are ascribed to electronic transitions between 5d-4f levels. The nature and activity of trap centers were evaluated from the parameters obtained from Chen′s peak shape method. The intense blue emission by phosphor makes it a competent material for blue emission display devices. Also, its thermoluminescence properties make it a good material for dosimetric applications.